Combining UV Lithography and an Imprinting Technique for Patterning Metal‐Organic Frameworks. (24th July 2013) - Doherty, Cara M.; Grenci, Gianluca; Riccò, Raffaele; Mardel, James I.; Reboul, Julien; Furukawa, Shuhei; Kitagawa, Susumu; Hill, Anita J.; Falcaro, Paolo
<x xml:space="preserve">Abstract</x> Thin metal‐organic framework (MOF) films are patterned using UV lithography and an imprinting technique. A UV lithographed SU‐8 film is imprinted onto a film of MOF powder forming a 2D MOF patterned film. This straightforward method can be applied to most MOF materials, is versatile, cheap, and potentially useful for commercial applications such as lab‐on‐a‐chip type devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>